Effect of Turning Angles on the Inflow Characteristics in a Waterjet Propulsion Pump - Li, Wei; Li, Shuo; Ji, Leilei (Journal of Modern Mechanical Engineering and Technology, 2023)
Abstract: To study the influence of turning maneuvering navigation angle on the inflow characteristics of water jet propulsion pumps, numerical simulations were conducted on mixed flow water jet propulsion pumps under straight and left and right 15 °/30 ° turning navigation states. By comparing the hydraulic performance differences of water jet propulsion pumps under five navigation states, the intrinsic relationship between turning angle and pump inflow morphology was elucidated, and the evolution mechanism of pump inflow morphology under straight navigation and turning conditions was emphasized, and conduct quantitative analysis on the inflow quality. The research results of this article provide a theoretical basis for selecting appropriate operating angles for ships under turning maneuvers.